The Application of Transit Passage Regime in Straits Used for International Navigation: A Study of the Straits of Malacca and Singapore - Rusli M.H.M. (2024)
The United Nations Convention on the Law of the Sea 1982 (LOSC) prescribes the application of the transit passage regime for vessels navigating via straits that connect one part of the high seas/exclusive economic zone (EEZ) to another part of the high seas/EEZ. The Straits of Malacca and Singapore fulfill this criterion if they are considered as one strait. Nevertheless, if both straits are considered as separate, then the situation would be different. This article discusses the types of navigational regimes in straits as prescribed by the LOSC and ventures into the potential legal and political implications that may arise should transit passage regime cease to apply in critical straits like the Straits of Malacca and Singapore. Indeed, the Straits of Malacca and Singapore are important sea lines of communication, and any interference with shipping would obviously disrupt the well-being of the global economy, particularly that of the Asia-Pacific region. 2012 Policy Studies Organization. Published by Wiley Periodicals, Inc.